2012
DOI: 10.1590/s1413-35552012005000014
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs of Brazilian physical therapists about chronic low back pain: a cross-sectional study

Abstract: Objectives: To measure the attitudes and beliefs of Brazilian physical therapists about chronic low back pain and to identify the sociodemographic characteristics that are more likely to influence these attitudes and beliefs. Methods: We conducted a cross-sectional study with 100 Brazilian physical therapists who routinely work with chronic low back pain patients. The attitudes and beliefs were measured by the Pain Attitudes and Beliefs Scale for Physiotherapists (PABS.PT) and the Health Care Providers' Pain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 34 publications
(57 reference statements)
2
35
3
4
Order By: Relevance
“…The result of these recent changes may be that treatment orientation of physiotherapists may be shifting towards to behavioural perspective. Also Magalhães, Costa, Cabral, and Machado (2012) reported that gender was significantly associated with the PABS-PT biomedical subscale. In their study males had a biomedical orientation.…”
Section: Discussionmentioning
confidence: 98%
“…The result of these recent changes may be that treatment orientation of physiotherapists may be shifting towards to behavioural perspective. Also Magalhães, Costa, Cabral, and Machado (2012) reported that gender was significantly associated with the PABS-PT biomedical subscale. In their study males had a biomedical orientation.…”
Section: Discussionmentioning
confidence: 98%
“…The mean and standard deviation scores for the biomedical and psychosocial scales were calculated on a “1 to 6” Likert scale and a “0 to 5” Likert scale to allow for comparison to the Magalhães et al, [14,21] study.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies have verified the two factor structure of the PABS.PT [18-21]. These studies have also explored other dimensions and related factors.…”
Section: Introductionmentioning
confidence: 97%
“…Segundo o Instituto Brasileiro de Geografia e Estatística, foi constatado que a dor lombar é a segunda doença crônica mais comum no Brasil. [2] Nos quadros crônicos de dor lombar, independentemente da presença ou não de doença, existe hipotrofia muscular, associada à fraqueza ou lesão dos tecidos moles da região. [3] O Prone Hip Extension (PHE) Test foi uma série de testes clínicos desenvolvidos por Vladimir Janda, consiste na extensão de quadril unilateral com o paciente pronado na maca, no qual são avaliados os músculos bíceps femoral (BF), glúteo máximo (GM), eretor contra-lateral (EC) e eretor ipsi-lateral (EI).…”
Section: Introductionunclassified